1994
DOI: 10.1111/j.1600-0773.1994.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effects of the Synthetic Thymic Dipeptide Pidotimod on the Immune System in the Aging Rat

Abstract: We have investigated the in vivo and in vitro effect of pidotimod, a synthetic thymic-derived drug, on the immune response in young (2 month-old), and aging (24 month-old) Sprague-Dawley rats. We studied the effect of different doses of pidotimod on the responsiveness of both cultured peripheral blood lymphocytes and splenocytes to mitogenic stimuli, as well as on interleukin-2 production by peripheral blood lymphocytes after stimulation with interleukin-1 and phytohemagglutinin. Treatment with pidotimod in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In addition, our data suggest that NGF could be used as a marker of breast cancer cells. The prognostic value of both p75 NTR and TrkA receptors (Descamps et al, 2001b) as well as the possibility of targeting p140 TrkAmediated mitogenic signaling with tamoxifen, a drug commonly used in breast cancer therapy, has already been reported (Chiarenza et al, 2001). Immunohistochemistry analysis of NGF in tumor biopsies revealed differences of intensity in the carcinomas studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our data suggest that NGF could be used as a marker of breast cancer cells. The prognostic value of both p75 NTR and TrkA receptors (Descamps et al, 2001b) as well as the possibility of targeting p140 TrkAmediated mitogenic signaling with tamoxifen, a drug commonly used in breast cancer therapy, has already been reported (Chiarenza et al, 2001). Immunohistochemistry analysis of NGF in tumor biopsies revealed differences of intensity in the carcinomas studied.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that nerve growth factor (NGF), the first discovered neurotrophic factor, is also a potent activator of both the survival and proliferation of breast cancer cells (Descamps et al, 1998(Descamps et al, , 2001a). In addition, the level of NGF receptor expression has some prognostic value (Descamps et al, 2001b) and the antiestrogen drug tamoxifen, which is widely used in breast cancer therapy, is able to inhibit the mitogenic effect of this neurotrophin in breast cancer cells (Chiarenza et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The trophic function of NGF for breast cancer cells, involving both mitogenic and antiapoptotic activities, has recently been shown (8,12). The prognostic value of both p75 NTR and TrkA receptors has also secondarily been reported (26), as has the possibility of targeting p140 TrkA -mediated mitogenic signaling with tamoxifen, a drug commonly used in breast cancer therapy (27). Our present data also suggest that targeting the p75 NTR /TRADD/NF-B signaling pathway may be a promising avenue for future treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-induced IL-2 secretion was also significantly greater in lymphocyte cultures from treated aged rats, but not in untreated 2 month-old rats. Moreover, the weight of the thymus resulted significantly higher both in young and old rats exposed to pidotimod than in controls (7)(8). In vitro stimulating activity of pidotimod on peripheral.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Chiarenza et al investigated the ex vivo effects of pidotimod on PBMC immune functions in ageing rats (24 months) compared to younger (2 months) and placebo treated animals (7)(8). Young and ageing rats underwent i.p.…”
Section: Animal Studiesmentioning
confidence: 99%